The CHD Protein Kismet Restricts the Synaptic Localization of Cell Adhesion Molecules at the Drosophila Neuromuscular Junction. - Smith, I.R.; Hendricks, E.L.; Latcheva, N.K.; Marenda, D.R.; Liebl, F.L.W. (International journal of molecular sciences, 2024)
The appropriate expression and localization of cell surface cell adhesion molecules must be tightly regulated for optimal synaptic growth and function. How neuronal plasma membrane proteins, including cell adhesion molecules, cycle between early endosomes and the plasma membrane is poorly understood. Here we show that the Drosophila homolog of the chromatin remodeling enzymes CHD7 and CHD8, Kismet, represses the synaptic levels of several cell adhesion molecules. Neuroligins 1 and 3 and the integrins ?PS2 and ?PS are increased at kismet mutant synapses but Kismet only directly regulates transcription of neuroligin 2. Kismet may therefore regulate synaptic CAMs indirectly by activating transcription of gene products that promote intracellular vesicle trafficking including endophilin B (endoB) and/or rab11. Knock down of EndoB in all tissues or neurons increases synaptic FasII while knock down of EndoB in kis mutants does not produce an additive increase in FasII. In contrast, neuronal expression of Rab11, which is deficient in kis mutants, leads to a further increase in synaptic FasII in kis mutants. These data support the hypothesis that Kis influences the synaptic localization of FasII by promoting intracellular vesicle trafficking through the early endosome.